Charpy impact properties of uni-directional carbon fiber-reinforced polymer tendons with protective layers. Issue 1 (January 2023) - Fang, Yawei; Fang, Zhi; Xiang, Yu; Feng, Lixin; Zhou, Xuhong
The present study explored potential forms of impact protection for carbon fiber-reinforced polymer (CFRP) tendons. Charpy impact tests were performed on CFRP rods and strands under protections of polyvinyl chloride (PVC) and poly-ethylen (PE). In the experimental program, the impact damage pattern and absorbed energy of CFRP tendons with and without external protection were obtained. The results show that the energy absorption capacity of CFRP tendons was improved under the protection of surface layers; and PE layers exhibited the highest protection effectiveness among all protection forms in terms of the increased absorbed energy and caused additional structural weight. Besides, two empirical expressions were established to quantify the relationship between the thickness of PE layers and the energy absorption capacity of the protected CFRP tendons, which may provide a simple tool to estimate the thickness of the layer required for the protection of a specific CFRP tendon in practical applications.